2016
DOI: 10.1002/suco.201500094
|View full text |Cite
|
Sign up to set email alerts
|

High‐cycle fatigue behaviour of reinforcing steel under the effect of ongoing corrosion

Abstract: High-cycle fatigue behaviour of reinforcing steel under the effect of ongoing corrosionThis paper presents the results of the corrosion fatigue behaviour of profiled reinforcing steel bars. Cyclically loaded rebar was simultaneously exposed to different corrosive environments -moderate to severe corrosive environments simulating XC or XD/XS exposure. Corrosion was configured naturally without any external polarization. Rebar was exposed to the corrosive solutions either directly or, when embedded in concrete, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 10 publications
0
6
0
1
Order By: Relevance
“…Several studies addressing the relationship between rib geometry, stresses at the rebar surface induced by service loads and the rebar fatigue performance have been conducted [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. The rib volume and the foot radius of the transverse rib were identified to have the main impact on the rebar fatigue performance.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies addressing the relationship between rib geometry, stresses at the rebar surface induced by service loads and the rebar fatigue performance have been conducted [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. The rib volume and the foot radius of the transverse rib were identified to have the main impact on the rebar fatigue performance.…”
Section: Introductionmentioning
confidence: 99%
“…Des Weiteren sorgt die Korrosion von Betonstahl in Beton für eine Aufrauung des Stahls und damit für eine Vielzahl an Mikrokerben, die zu einem verfrühten Versagen bei kombinierter Einwirkung mit Dauerschwingen führen können. Dies zeigten Untersuchungen an in Lösung [11] sowie einbetoniert [12, 13] geschwungenen Betonstahlproben.…”
Section: Allgemeinesunclassified
“…Garbatov et al (2014) conducted fatigue strength experiments on corroded rebars and found a direct relationship between the initial corrosion surface roughness and the pit depth. Gehlen et al (2016) demonstrated that the slope of the S-N curve was steeper in a corrosion fatigue environment for rebar. Lan et al (2018) proposed a Weibull model of the C-S-N (Corrosion S-N) relationship for steel rebar, which was subsequently utilized to evaluate the influence of corrosion on the fatigue life.…”
Section: Introductionmentioning
confidence: 97%